2004
DOI: 10.1093/hmg/ddh338
|View full text |Cite
|
Sign up to set email alerts
|

HNF1 β/TCF2 mutations impair transactivation potential through altered co-regulator recruitment

Abstract: Mutations in the HNF1beta gene, encoding the dimeric POU-homeodomain transcription factor HNF1beta (TCF2 or vHNF1), cause various phenotypes including maturity onset diabetes of the young 5 (MODY5), and abnormalities in kidney, pancreas and genital tract development. To gain insight into the molecular mechanisms underlying these phenotypes and into the structure of HNF1beta, we functionally characterized eight disease-causing mutations predicted to produce protein truncations, amino acids substitutions or fram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
79
1
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(83 citation statements)
references
References 36 publications
1
79
1
2
Order By: Relevance
“…We have reported that this difference may be caused by the difference in DNA binding affinity (Kitanaka et al 2004). The dominant-negative effect of R177X mutant on wildtype HNF-1b has also been reported to differ with cells and promoters (Tomura et al 1999, Barbacci et al 2004, Gu et al 2004. From these observations, we consider that analyses of the intended native promoters in combination with wild-type HNF-1b and HNF-1a are essential to investigate the function of HNF-1b mutants.…”
Section: Discussionmentioning
confidence: 91%
“…We have reported that this difference may be caused by the difference in DNA binding affinity (Kitanaka et al 2004). The dominant-negative effect of R177X mutant on wildtype HNF-1b has also been reported to differ with cells and promoters (Tomura et al 1999, Barbacci et al 2004, Gu et al 2004. From these observations, we consider that analyses of the intended native promoters in combination with wild-type HNF-1b and HNF-1a are essential to investigate the function of HNF-1b mutants.…”
Section: Discussionmentioning
confidence: 91%
“…In addition to these phenotypes, variable levels of pancreas atrophies have recently been associated with different TCF2 mutations (19,20). Remarkably, we have recently identified a severe pancreas hypoplasia in two fetuses carrying previously undescribed mutations in the TCF2 gene (A. L. Delezoide, C.H., and S.C., unpublished results).…”
mentioning
confidence: 75%
“…These results might indicate that there is a relatively high threshold for sufficient transcription, or alternatively, the activation level could be gene-specific and the expression of essential genes is below the level needed for proper development and function with the mutant. It has been reported that the R295H mutant exhibited target-specific effects of activation in which the transactivation potential of R295H on the HNF4α promoter reached to wild-type transactivation level, while transactivation of either Afp or albumin promoter by this mutant were barely detectable (49). In other studies, the corresponding mutants R263C/L in HNF1α showed greatly reduced DNA binding activity as a result of these more drastic substitutions (52,53).…”
Section: Disease-related Mutationsmentioning
confidence: 91%
“…These effects on transcriptional activity could be gene-specific or synergistic partner-dependent. It has been reported that the effects on transcription of some of these mutants, especially those that do not affect or only weakly affect the DNA-binding activity, correlate with the loss of association with the transcriptional coregulators such as CBP or PCAF (49). Thus, even though the molecular bases of the functional disruptions have been elucidated, other mechanistic details that might be exploited for intervention await additional studies.…”
Section: Disease-related Mutationsmentioning
confidence: 99%